Women with Cervical Cancer: Perceptions about the Papanicolaou Test - María-Teresa Urrutia; Lauren Poupin (Universidad de La Sabana, 2015)
Objective: Examine perceptions about the Papanicolaou (Pap) test from the perspectives of Chilean women with cervical cancer. Design: A descriptive, cross-sectional study conducted in Santiago, Chile. Participants: 127 Chilean women. Results: The principal reasons for not having had a PAP test were procrastination and barriers related to fear, embarrassment, discomfort, not caring, lack of time, and lack of knowledge. Conclusion: All the reasons given by the Chilean women who took part in the study must be considered by health care professionals who are in a position to advocate for education and cervical cancer screening for women, especially in countries where the disease is still prevalent. These results can serve as a guide for education programs and can be applied in intervention research. doi: 10.5294/aqui.2015.15.4.5